INDOOR OUTDOOR ULTRAFINE PARTICLE MEASUREMENTS IN LECTURE ROOMS - Wardoyo, Arinto Y.P.; Santjojo, Djoko H.; Putri, Inggita I.H. (Department of Physics - Faculty of Science, 2013)
Ultrafine partilces (UFP) has become important concerns of people due their identified impacts on human health. The contribution of UFP on indoor air quality (IAQ) is another thing that attracts an attention for investigation. This study performs the measurements of outdoor indoor UFP concentrations in lecture rooms. The aims were to measure the UFP concentrations in the lecture rooms, and also to estimate the relationships between outdoor UFP concentrations and indoor UFP concentrations. The results showed that the UFP concentration in the lecture rooms varied between 1.0 x 103 particles/cm3 and 4.1 x 103 particles/cm3. The indoor UFP concentrations were found proportional to the outdoor UFP concentrations. And I/O UFP concentration ratio was obtained more than 80 %.